Update on the Epidemiology of Pulmonary Nontuberculous Mycobacterial Infections - Kendall, Brian A.; Winthrop, Kevin L. (Seminars in Respiratory and Critical Care Medicine, 2013)
For decades, the incidence of pulmonary nontuberculous mycobacteria (NTM) has been reported to be increasing, yet formal epidemiological evaluation of this notion has been lacking until recently. Defining the epidemiology of NTM has been more challenging than with Mycobacterium tuberculosis (MTB). Unlike MTB, NTM are soil and water organisms, and infection is thought to be acquired from the environment rather than transmitted from person-to-person, with very rare exceptions. Due to their nearly ubiquitous presence in municipal water supplies, exposure to NTM is common. Further, NTM can colonize the respiratory tract without causing disease. NTM disease is not reportable to public health authorities; therefore, epidemiological and surveillance data are not readily available. Nonetheless, the prevalence of pulmonary NTM disease has increased dramatically in the United States and globally over the past 3 decades. Mycobacterium avium complex (MAC) accounts for the majority of NTM infections worldwide, but there is significant regional variability of various species. Additionally, novel species have been implicated in several countries in NTM pulmonary disease.
Keywords: nontuberculous mycobacteria; epidemiology; Mycobacterium avium; Mycobacterium tuberculosis